Digital Coalescence and Consolidated Geoconservation Outcomes: A Case Study Using ArcGIS Mobile Applications at Tasmanian Coastal Geoconservation Sites - Jake Crisp; Joanna Ellison; Andrew Fischer (Geoconservation Research)
Geoconservation outcomes are hindered by highly subjective and conflicting criteria, varying assessment objectives, disparities in geoconservation strategy steps and the inadequate capturing and representation of geological data in dynamically changing inventories. Review shows that geoconservation outcomes are further hindered by the exclusion of quantitative geodiversity assessment from geoconservation strategies. A geoconservation toolkit is presented using the ArcGIS mobile apps QuickCapture, Survey123 and Explorer to consolidate the steps in achieving geoconservation outcomes. The toolkit closed the theoretical gap between geodiversity assessment and geoconservation strategies and attenuated the discrepancies in geoconservation strategy protocols. Preliminary research suggests the inclusion of geodiversity in geoconservation strategies will benefit geoconservation outcomes by providing scholars with a proxy to predict inventorying and geoheritage values, conservation exigencies and site complexity. The toolkit consolidated separate geoconservation strategies by unifying individual steps into one distinctive process leading to streamlined inventorying, geodiversity and geoheritage assessment. ArcGIS QuickCapture facilitated challenges in managing dynamically changing inventories by providing a fast and streamlined approach to the capturing of geodiversity information and locations. ArcGIS Survey123 facilitated the amalgamation of steps in geodiversity and geoheritage assessment and inventorying. ArcGIS Survey123 also facilitated the introduction of a suitability analysis tool to objectively manage and select existing geoheritage and inventorying criteria. Subsequent research would augment this study and its findings by determining whether statistical correlations exist between geodiversity and associated inventory and geoheritage values. Ensuing research would then seek expert advice on the standardisation of which strategies, criteria, methodologies, and processes to include in an all-encompassing third-party mobile GIS application to complement the toolkit concept in this study.